The pathological pebrine diseases of Bombyx mori caused by Nosema bombycis (mNb) in South Sulawesi, Indonesia - SITTI NURAENI; ANDANG SURYANA SOMA; ANDI SADAPOTTO; ANDI MUJETAHID; BAHARUDDIN BAHARUDDIN; RYZA JAZID BAHARUDDIN NUR; NURUL HUDA; ABDUL FATTAH (Society for Indonesian Biodiversity, 2024)
Abstract. Nuraeni S, Soma AS, Sadapotto A, Mujetahid A, Baharuddin, Nur RJB, Huda N, Fattah A. 2024. The pathological pebrine diseases of Bombyx mori caused by Nosema bombycis (mNb) in South Sulawesi, Indonesia. Biodiversitas 25: 2990-2995. South Sulawesi is the main producer of raw silk in Indonesia. However, over the past decade, raw silk production has plummeted due to an epizootic of pebrine disease. Pebrine disease is caused by the obligate parasite microsporidium Nosema bombycis Filatova, 1942 (mNb) (Microsporidia: Nosematidae). This study aims to identify mNb spore morphology and pathological characteristics, including disease symptoms, infectivity tests, and pebrine epizootic history. Spore morphology was observed using a light microscope. Infectivity test with a spore concentration of 1×108 mL-1 in 3rd, and 4th instars, inoculation using the smear method on mulberry leaves. Information on pebrine disease rates was obtained from documents of egg certification between 2002 and 2016. The research results show that the spores are oval in shape. The size of the spores can reach a length of 4.57±0.46 µm and a width of 2.24±0.493 µm. The main symptoms of this disease are the change in color of the cuticle to brownish with irregular black spots and non-uniform growth because many fail to molt, and the larval phase increases by 8-10 days. Inoculation in the 3rd instar can cause larval death starting on the second day after inoculation, with a cumulative mortality rate of 64%. Inoculation of the 4th instar, death begins on the eighth day, and a cumulative mortality rate of 52%. The pebrine epizootic in 2010 reached 72.42%, which reduced production by 57%. Understanding the pathological causes of pebrine disease and its history is useful to prevent rather than control the occurrence of the next epizootic.